Historien, tiden og fortiden. Om billedet af historieskrivningen i Oplysningstiden - Eskildsen, Kasper Risbjerg (Passage - Tidsskrift for litteratur og kritik, 2018)
Kasper Risbjerg Eskildsen: “History, Time, and the Past. On the Image of History Writing in the Enlightenment” During the 18th century, the image of the historian changed dramatically. The proper historian was no longer a man of the world, who wrote from personal experience, but a professional, who gained his authority from his training and academic background. The essay investigates this transformation through images of history writing and argues that the shift in the image of the historian was connected to a new sense of the precarity of the past and to a new divide between history and the past. *Online-version adskiller sig fra den trykte version.